Integrated Sustainability Assessment: Exergy, Emergy, Life Cycle Assessment - Cano-Londoño, Natalia; Heriberto, Cabezas; Krisztián, Baracza (Frontiers in Sustainability, 2022)
Methodological tools such as Life Cycle Assessment (LCA), Exergy Analysis (ExA) and Emergy Analysis (EmA) that account for sustainability indicators in environmental, economic, and/or social dimensions, cannot provide an assessment under these three dimensions in a robust way by themselves. This research is proposing a sustainability assessment framework to obtain a unified performance metric (Integrated Sustainability Index, ISI) to assess Triple Bottom Line – TBL. LCA, ExA and EmA indicators are implemented in a complementary but not interchangeable manner, providing additional information for sustainability decision making. The systematic approach is on a conceptual definition and calculation of sustainable environmental, social and economic disaggregated indicators. These are then systematically combined into an Integrated Sustainability Index (ISI). EmA evaluates sustainability from a 'donor-side' perspective, by assigning values to the environmental efforts and investment of nature to make and support flows, materials, and services; the system boundary is the geosphere. ExA evaluates sustainability through exergy efficiency under a "user-side" evaluation process (system boundary is the technosphere). LCA evaluates it based on the quantification of environmental impact by water, soil and air emissions, caused by the use and processing of resources to provide products or services as a "user-side" method. The proposed sustainability index presents a comprehensible hierarchic structure supported by LCA, ExA, and EmA methodologies. The integration of social, environmental, and economic components into an index that also allows for the adjustment of externalities reducing the risk of subjectivity is a new approach to assessing sustainability.